Association of oxidative balance score, cardiovascular, and all-cause mortality among patients with type 2 diabetes mellitus - Ni, Chengming; Wang, Xiaohang; Zhou, Yunting; Wang, Qianqian; Cai, Zhensheng; Wang, Huan; Chen, Yang; Liu, Yu; Sun, Zilin (Frontiers in Endocrinology, 2024)
To investigate the association between oxidative balance score (OBS), cardiovascular mortality (CVM), and all-cause mortality (ACM) in type 2 diabetes mellitus (T2DM) patients.We included 6,119 participants with T2DM from the 2005-2020 National Health and Nutrition Examination Surveys (NHANES). The status of CVM and ACM of participants was followed through December 31, 2019. Multivariable Cox regression models, Kaplan-Meier curves, log-rank test, restricted cubic spline regression, and subgroup analysis, were used to evaluate the relationship between OBS, CVM, and ACM.During a median of 100.9 months follow-up, 1,790 ACM cases had occurred, 508 of which were due to cardiovascular disease. The T2DM participants were divided into four groups based on the quartiles of OBS. Participants with Q4 tended to be younger, financially better-off, married, highly educated, had lower alcohol consumption rates, were non-smokers, and exhibited a lower likelihood of ACM and CVM. In multivariate Cox regression models, compared with the patients with Q4, those with Q1 had a 30% increased risk for ACM (Q1, reference; Q4, HR: 0.70, 95%CI: 0.58-0.86) and a 43% increased risk for CVM (Q1, reference; Q4, HR: 0.57, 95%CI: 0.36-0.88). The restricted cubic spline regression models have no nonlinear relationship between OBS, CVM, and ACM. Kaplan-Meier survival curves showed that patients with Q4 had a lower risk of ACM and CVM (log-rank P < 0.05).We find that ACM and CVM increase with higher OBS in T2DM patients. Moreover, there are linear relationships between OBS, ACM, and CVM.